2019
DOI: 10.1007/978-3-030-29736-7_59
|View full text |Cite
|
Sign up to set email alerts
|

Auditing the Accessibility of MOOCs: A Four-Component Approach

Abstract: This paper reports the design of a four-component audit to evaluate the accessibility of Massive Open Online Courses (MOOCs). The MOOC accessibility audit was designed as part of a research programme at The Open University (UK) that aimed to assess the current state of accessibility of MOOC platforms and resources, to uncover accessibility barriers, and to derive recommendations on how the barriers could be addressed. The audit is composed of four evaluation components: technical accessibility, user experience… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 6 publications
(9 reference statements)
0
5
0
Order By: Relevance
“…The new version of PEC2 requires greater focus and knowledge of WCAG by the students and this is reflected in the scores. Now students must be more proactive in evaluating each of the accessibility success criteria using the new checklist [ 62 ]. It is a positive aspect of the redesign as the students learn how to use WCAG, but it requires a greater commitment on their part to invest more time in the activities.…”
Section: Resultsmentioning
confidence: 99%
“…The new version of PEC2 requires greater focus and knowledge of WCAG by the students and this is reflected in the scores. Now students must be more proactive in evaluating each of the accessibility success criteria using the new checklist [ 62 ]. It is a positive aspect of the redesign as the students learn how to use WCAG, but it requires a greater commitment on their part to invest more time in the activities.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the review of the 31 identified studies, 16 papers conducted assessments to evaluate the accessibility of OER, while the 15 remaining papers did not conduct any assessment. Specifically, to assess the accessibility of OER, three different methods were used, as shown in Using manual evaluation method Questionnaires Avila Caruso & Ferlino, 2009;Mulwa et al, 2016;Navarrete & Luján-Mora, 2015a;Navarrete et al, 2019;Navarrete & Luján-Mora, 2018;Sanchez-Gordon & Luján-Mora, 2016 No assessment N/A Coughlan et al, 2016;Hejer et al, 2017;Iniesto and Rodrigo, 2018;Iniesto & Rodrigo, 2016;Iniesto et al, 2017;Iniesto et al, 2019;Kourbetis & Boukouras, 2014;Kourbetis et al, 2016;Morales and Benedi, 2017;Moreno et al, 2018;Navarrete et al, 2016;Politis et al, 2014;Sanchez-Gordon & Luján-Mora, 2015;Yalcinalp & Emiroglu, 2012;Zervas et al, 2014 aDesigner, used by Iniesto and Rodrigo (2014) and , aimed to simulate the use by people with visual disabilities in order to help the designer assess the extent to which a given content is accessible to users with that particular disability. Finally, manual assessment is mostly based on users' questionnaires (Avila Caruso & Ferlino, 2009;Mulwa et al, 2016;Navarrete et al, 2019;Navarrete & Luján-Mora, 2015a;Navarrete & Luján-Mora, 2018;Sanchez-Gordon & Luján-Mora, 2016).…”
Section: Assessment Methodologies Usedmentioning
confidence: 99%
“…Other strategies include the adoption of a variety of assessment types to prevent cheating: reflective pieces, blogs, quizzes, essays related to applying learning to practice, projects (Von Gruenigen et al, 2018); and distributing assessment across various types rather than having one high-stakes assessment (Bretag et al, 2019). Iniesto et al (2019) also underline the relevance of evaluating accessibility in educational settings, so that assessment is accessible to all learners.…”
Section: Types Of Assessments Applied In Existing Practicesmentioning
confidence: 99%